Prevention of Atopic Dermatitis in Mice by Lactobacillus Reuteri Fn041 Through Induction of Regulatory T Cells and Modulation of the Gut Microbiota. Issue 6 (23rd January 2022) - Zhao, Yuning; Qi, Ce; Li, Xinyue; Lu, Mengyao; Zhang, Haowen; Zhou, Jingbo; Dang, Hongyang; Chen, Jie; Li, Shuangqi; Sun, Jin; Yu, Renqiang; Li, Duo
Abstract : Scope: The development of atopic dermatitis (AD) in infants is closely related to the lagging development of intestinal microbiota, including that inoculated by breast milk bacteria, and immune development. Lactobacillus reuteri Fn041 is a secretory immunoglobulin A (sIgA) ‐coated bacterium derived from human milk. Methods and Results: We intervene with L. reuteri Fn041 in maternal and offspring BALB/C mice during late gestation and lactation and after weaning of the pups, respectively. AD is then induced with MC903. L. reuteri Fn041 significantly suppresses AD symptoms such as skin swelling, mast cell, and eosinophil infiltration. This effect is attributed to the regulation of the systemic Th1 and Th2 cytokine ratios and the promotion of CD4 + CD25 + Foxp3 + regulatory T cell proliferation in mesenteric lymph nodes. It is also associated with the regulation of intestinal microbiota, particularly promoting Lactobacillus and Akkermansia . Conclusion: Our study strengthens the understanding that breast milk‐derived sIgA coated potential probiotics are involved in the development of infant intestinal microbiota, thus promoting immune development and preventing allergic diseases, and expanding the knowledge of breast milk sIgA and bacterial interactions on infant immune development. Abstract : Secretory immunoglobulin A (sIgA)‐coated Lactobacillus reuteri Fn041 from breast milk prevents the occurrence of atopic dermatitis by regulating the balance of Th1 and Th2 immune responses, inducing the production of regulatory T cells and reshaping intestinal microbiota.